2000
DOI: 10.1134/1.1311992
|View full text |Cite
|
Sign up to set email alerts
|

Improved phenomenological renormalization schemes

Abstract: An analysis is made of various methods of phenomenological renormalization based on finite-size scaling equations for inverse correlation lengths, the singular part of the free energy density, and their derivatives. The analysis is made using two-dimensional Ising and Potts lattices and the three-dimensional Ising model. Variants of equations for the phenomenological renormalization group are obtained which ensure more rapid convergence than the conventionally used Nightingale phenomenological renormalization … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
(65 reference statements)
0
9
0
1
Order By: Relevance
“…The upper bound was found by an analysis of the asymptotic properties of self-avoiding random walks on the lattice under consideration. More recently, Yurishchev [7] derived upper and lower bounds on the critical temperature by using the transfer-matrix technique and an extended phenomenological renormalization group theory approach [8,9]. Yurishchev showed that for a relatively small anisotropy ( 510 À3 ) the accuracy of equation (1) is rather low.…”
Section: Introductionmentioning
confidence: 99%
“…The upper bound was found by an analysis of the asymptotic properties of self-avoiding random walks on the lattice under consideration. More recently, Yurishchev [7] derived upper and lower bounds on the critical temperature by using the transfer-matrix technique and an extended phenomenological renormalization group theory approach [8,9]. Yurishchev showed that for a relatively small anisotropy ( 510 À3 ) the accuracy of equation (1) is rather low.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the transfer matrices for which the eigenproblems was solved were dense matrices of sizes up to 65 536 × 65 536. To solve the eigenproblem we took into account the internal and lattice symmetries of subsystems and used the block-diagonalization method (see, e. g., [9,7]). Calculations were performed on an 800 MHz Pentium III PC running the FreeBSD operating system.…”
Section: Resultsmentioning
confidence: 99%
“…locate T c more accurately in comparison with the ordinary RG equation ( can be evaluated by standard formulas via the eigenvalues and eigenvectors of transfer matrices (see, e. g., [7,8,9]).…”
Section: Basic Equationsmentioning
confidence: 99%
“…In other words, the amplitudes of all finite-size corrections to the critical internal energy of a system u ∞ (K c ) are equal to zero. For the square isotropic Ising lattice, the derivative of the inverse correlation length κ L (K) with respect to a temperature-like variable K has a similar property [20,21]:…”
Section: Discussionmentioning
confidence: 99%